Documentation: CIDOC Database Survery. - Case, Mary (Museum Management & Curatorship)
The article provides information on the Database Survey on Working Group of ICOM International Committee for Documentation (CIDOC). It notes that the group undertakes a world wide survey of museums using computers for collection documentation. It is said that the group built an Advisory Panel of museum professionals willing to share documentation information with other museums. An overview on the how the survey is conducted is also presented.